Overuse injuries of the pediatric and adolescent throwing athlete - Tisano, B. K.; Estes, A. R. (Medicine & Science in Sports & Exercise, 2016)
In the hypercompetitive environment of year round youth baseball, arm pain is commonplace. Although much research has been done about injuries in the overhead throwing athlete, the emphasis has been on the more elite levels, where athletes have reached full development. The anatomy of the skeletally immature athlete, including open physeal plates and increased tissue laxity, raises unique issues in the presentation and treatment of repetitive throwing injuries of the elbow and shoulder. With a focus on "little leaguers," this discussion evaluates five of the most common elbow and shoulder injuries—Little Leaguer`s elbow, ulnar collateral ligament sprain or tear, osteochondritis dissecans/Panner`s disease, Little Leaguer`s shoulder, and multidirectional instability. In the developmentally distinct pediatric athlete, pathogenesis, diagnosis, and treatment may differ from that established for adults. Offering early diagnosis and treatment appropriate to a child`s level of development will enable youth to not only continue to play sports but to also maintain full functionality as active adults.